2020
DOI: 10.1186/s12877-020-01803-5
|View full text |Cite
|
Sign up to set email alerts
|

Older age and frailty are the chief predictors of mortality in COVID-19 patients admitted to an acute medical unit in a secondary care setting- a cohort study

Abstract: Background There is a need for more observational studies across different clinical settings to better understand the epidemiology of the novel COVID-19 infection. Evidence on clinical characteristics of COVID-19 infection is scarce in secondary care settings in Western populations. Methods We describe the clinical characteristics of all consecutive COVID-19 positive patients (n = 215) admitted to the acute medical unit at Fairfield General Hospital (secondary care setting) between 23 March 2020 and 30 April… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
87
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(99 citation statements)
references
References 30 publications
8
87
3
1
Order By: Relevance
“…Three small and underpowered studies showed no association [14][15][16]. Given recent articles exploring this association between frailty and mortality [17][18][19][20][21][22][23], we believe that there is an urgent need to summarize the evidence of this important issue. The objective of our study is to systematically review and quantify the results of the associations between frailty and mortality, which could provide evidencebased suggestions for clinicians.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Three small and underpowered studies showed no association [14][15][16]. Given recent articles exploring this association between frailty and mortality [17][18][19][20][21][22][23], we believe that there is an urgent need to summarize the evidence of this important issue. The objective of our study is to systematically review and quantify the results of the associations between frailty and mortality, which could provide evidencebased suggestions for clinicians.…”
Section: Introductionmentioning
confidence: 94%
“…A global pandemic of coronavirus disease 2019 (COVID- 19) was first reported in Wuhan city, China, in December 2019 [1]. The total number of confirmed cases was 96,877, 399 worldwide on 23 January 2021 (https://www.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, studies reporting the association of frailty with poor outcomes in the COVID-19 pandemic have shown conflicting results. Although frailty was associated with increased mortality in multiple studies [ 3–9 ], in some studies it was not [ 2 , 10 ]. Potential explanations for these inconsistent findings may be of a methodological nature, including differences in patients’ selection (partially due to different healthcare systems), relatively small sample sizes and single-centre studies.…”
Section: Introductionmentioning
confidence: 99%
“…COVID-19 has worse outcomes in older persons especially if they are frail ( 1 – 3 ). Persons with hypertension, diabetes mellitus, and heart failure also have worse outcomes.…”
mentioning
confidence: 99%